2008
DOI: 10.1089/aid.2007.0180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose IL-2 Immunotherapy on Frequency and Phenotype of Regulatory T Cells and NK Cells in HIV/HCV-Coinfected Patients

Abstract: We evaluated the effect of low-dose IL-2 therapy (daily 1.2 MIU/m(2), subcutaneously) on the number and phenotype of regulatory T cells (T(regs)) and natural killer (NK) cells in HIV/HCV-coinfected patients taking antiretroviral therapy. The frequency and phenotype of circulating T(regs) (defined as CD3(+) CD4(+) CD25(high) or CD3(+) CD4(+) FOXP3(+)) and NK cells (CD3(-) CD16(+)/CD56(+)) were evaluated at baseline and after 12 weeks of treatment. The expression of CD25, CTLA-4, and granzymes A and B by CD4(+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…Experimental evidence suggest several possibilities to account for this observation: (i) chronic expansion of Treg in vivo results in low levels of CD25 expression, retaining their suppressive activity, as previously reported in a murine model [35]; this constant expansion (high Treg frequency) is observed also in GALT from HIV infected patients [5, 30]; (ii) it might reflect internalization of the CD25 molecule after IL-2 binding [36]; in fact, the expansion of CD4 + CD25 lo CD127 lo Foxp3 + Treg is one of the long-term effects of IL-2 therapy in HIV patients [37, 38]; (iii) in vitro assays have shown that HIV induces down regulation of the CD25 molecule in CD4 + infected cells [39]. In addition, HIV viral proteins are involved in this process, inhibiting IL-2R expression; HIV p29 protein induces a two fold increase in the intracellular cyclic adenosine 3’,5’-monophosphate (cAMP) in PBMC which is associated with the decrease of CD25 [40].…”
Section: Discussionsupporting
confidence: 61%
“…Experimental evidence suggest several possibilities to account for this observation: (i) chronic expansion of Treg in vivo results in low levels of CD25 expression, retaining their suppressive activity, as previously reported in a murine model [35]; this constant expansion (high Treg frequency) is observed also in GALT from HIV infected patients [5, 30]; (ii) it might reflect internalization of the CD25 molecule after IL-2 binding [36]; in fact, the expansion of CD4 + CD25 lo CD127 lo Foxp3 + Treg is one of the long-term effects of IL-2 therapy in HIV patients [37, 38]; (iii) in vitro assays have shown that HIV induces down regulation of the CD25 molecule in CD4 + infected cells [39]. In addition, HIV viral proteins are involved in this process, inhibiting IL-2R expression; HIV p29 protein induces a two fold increase in the intracellular cyclic adenosine 3’,5’-monophosphate (cAMP) in PBMC which is associated with the decrease of CD25 [40].…”
Section: Discussionsupporting
confidence: 61%
“…To date, there has only been one documented report looking at the proportion of circulating CD4 ϩ Tregs during HCV/HIV co-infection (42). This study examined the effect of IL-2 immunotherapy on the frequency and phenotype of Tregs in HCV/HIV co-infected patients.…”
Section: Fig 3 (A)mentioning
confidence: 99%
“…Moreover, administration of a similar IL-2/Ig plasmid in macaques results in a dramatic increase in CD25 + T cells [50]. In addition, low-dose IL-2 therapy in HIV-1-infected patients results in expansion and activation of Treg [99]. Taken together, these data raise the possibility that the co-administration of the IL-2/IgG plasmid with the gag p15/p26 plasmid in the current study could have elicited Gag-specific Treg that suppressed potentially protective Gag-specific immune responses in the vaccinates.…”
Section: Discussionmentioning
confidence: 99%